Azolla sporophytes and spores from the late cretaceous and Paleocene of Patagonia, Argentina - Hermsen, Elizabeth J. (2019)
Premise of research. While Azolla has a rich fossil record based on dispersed megaspore apparatuses and microspore massulae, fossil sporophytes are relatively rare. In this contribution, we describe two fossil Azolla species based on both sporophytes and spores from Chubut Province, Patagonia, Argentina: Azolla coloniensis De Benedetti & Zamaloa, emend. Hermsen et al., and A. keuja Jud et al., sp. nov. Azolla coloniensis and A. keuja are the first fossil species of Azolla to be represented by vegetative structures (i.e., leaves, stems, and roots) from both South America and the Southern Hemisphere. Methodology. We examined sporophyte material of A. coloniensis from the Cañadón del Irupé locality, Upper Cretaceous, La Colonia Formation, and A. keuja from the Palacio de los Loros locality PL-2, Paleocene, Salamanca Formation. Spores of A. keuja were obtained from a sporophyte specimen and its surrounding rock matrix. Material was studied using standard light microscopy, epifluorescence microscopy, and scanning electron microscopy. Fossils are held at the Museo Paleontológico Egidio Feruglio, Trelew, Chubut Province, Argentina. Pivotal results. Azolla coloniensis produced many-floated megaspore apparatuses and microspore massulae with anchor-tipped glochidia, placing it in the fossil Azolla section Florschuetzia. Azolla keuja sporophytes are structurally similar to those produced by the extant African species A. nilotica and the Late Cretaceous–Paleocene North American species A. schopfii in overall size, growth form, leaf structure, and production of fascicled roots; while all three taxa produce similar microspore massulae, the structure of their megaspore apparatuses differ. Azolla keuja cannot be assigned to any section of Azolla. Conclusions. Azolla coloniensis and A. keuja are important because they provide two new organismal concepts for extinct species of Azolla. Our inability to fully classify A. keuja to section, in combination with the great morphological diversity of fossil Azolla, indicates that a comprehensive reevaluation of phylogeny and taxonomy that incorporates both extant and fossil species is needed.